Maintaining Students' Performance through Exhibition: Reporting Project of English Instructional Technologies course - Ahmad, Arimuliani; Rezki, Rezki; Khulaifiyah, Khulaifiyah (ELT-Lectura, 2024)
Pre-service teachers are expected to master content knowledge, pedagogical factor, communication skills, classroom management, critical thinking and problem-solving, collaboration and teamwork, reflective practice and technology integration. To achieve that target, teaching and learning process should be organized to facilitate activities that can improve their learning experiences. Exhibition can be implemented to provide valuable feedback and insights that can be used to improve future exhibitions or make informed decisions regarding the current one. Besides, this chance can also maximize to maintain students' performance in creative and engaging approach. This study aims to expose how the researcher manage an exhibition from students’ project to enhance their performance in English Instructional Technology course. The results demonstrate that pre-service teachers had a moderately satisfactory amount of mentorship experience, with modeling and pedagogical knowledge receiving among the lowest mean scores.